PURIFIKASI PROTEIN IMUNOGENIK 31 DAN 56 kDa DARI KELENJAR SALIVA Aedes aegypti - Syubbanul Wathon; Fitria Mutiah; Rike Oktarianti; Kartika Senjarini (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
Purification of 31 and 56 kDa Immunogenic ProteinsÂ from the Salivary Glands of Aedes aegyptiThe salivary gland of arthropod vector contains various bioactive compounds and plays a role in the transmission of pathogens to the host. The host develops anti-salivary antibodies against vector saliva exposure. Our previous research has identified two immunogenic proteins with molecular weights of 31 and 56 kDa from the Aedes aegypti salivary gland protein extract. However, the role of the 31 and 56 kDa immunogenic proteins from saliva Ae. aegypti is not fully known, so it is necessary to purify two immunogenic protein fractions to better specify the target of developing a dengue vaccine. This study aimed to purify the 31 and 56 kDa immunogenic protein fractions by electroelution and dialysis methods. The purification of the two protein fractions has been successful which were confirmed by the SDS-PAGE by the existence of single-band parallel to the positive control. These results were further supported by the dot blot analysis which showed a positive reaction in the form of dark spots in the two protein fractions which were reacted with dengue patients' serum, endemic healthy people, and neonates. These results indicated that the purified 31 and 56 kDa immunogenic protein fraction can be identified by specific antibodies.Keywords: dialysis, electroelution, immunogenic, purification, saliva Â ABSTRAKKelenjar saliva vektor arthropoda mengandung berbagai senyawa bioaktif dan berperan dalam transmisi patogen ke tubuh inang. Tubuh inang mengembangkan antibodi anti-saliva terhadap paparan saliva vektor. Penelitian kami sebelumnya telah mengidentifikasi dua protein imunogenik dengan berat molekul 31 dan 56 kDa dari ekstrak protein kelenjar saliva Aedes aegypti. Namun demikian, peranan protein imunogenik 31 dan 56 kDa dari saliva Ae. aegypti belum diketahui sepenuhnya sehingga perlu dilakukan purifikasi dua fraksi protein imunogenik untuk lebih menspesifikkan target pengembangan vaksin dengue. Tujuan penelitian ini untuk melakukan purifikasi fraksi protein imunogenik 31 dan 56 kDa melalui metode elektroelusi dan dialisis. Keberhasilan purifikasi dua fraksi protein 31 dan 56 kDa terbukti dari hasil konfirmasi SDS-PAGE dengan terbentuknya pita tunggal sejajar dengan kontrol positif. Hasil tersebut diperkuat dengan analisis dot blot yang menunjukkan reaksi positif dengan munculnya noktah gelap pada dua fraksi protein tersebut ketika direaksikan dengan serum pasien DBD, penduduk sehat endemik dan neonatus. Hasil ini mengindikasikan bahwa fraksi protein imunogenik 31 dan 56 kDa hasil purifikasi dapat dikenali oleh antibodi spesifik.